DISASTER MITIGATION AND GEOLOGY AWARENESS AT ADIDARMA 15 SENIOR HIGH SCHOOL, BANDA ACEH CITY - Joyontono, Puncak; Rangkuti, Nazla Syafitri; Hapsari, Tika; Zahratunnisa, Zahratunnisa; Salsabila, Rifa Salma; Hasanah, Uswatun; Hidayati, Dian Meutia; Harun, Nurul Azmi (Universitas Syiah Kuala, 2025)
Adidarma 15 Senior High School in Banda Aceh is situated in an area vulnerable to seismic and tsunami disasters, as indicated by the BPBAs Disaster Map. Established in 1983, the school suffered significant damage during the Aceh Earthquake and Tsunami in 2004. Additionally, the schools physical environment contributes to its vulnerability to disasters; it lies approximately 20 meters above sea level, 34 kilometers from the coastline, and 12 kilometers from the river banks. Being located in an urban area surrounded by buildings, restricts the space for emergency responses during disasters.As a public facility, it has vulnerable objects to disasters. There are at least 152 students and a number of school staff who need to be protected from the disasters (earthquakes and tsunamis). They have activity in 5 buildings which have 2-storey buildings which have no supporting facilities for disaster mitigation in the school environment.At Adidarma 15 Senior High School, disaster mitigation efforts represent a commitment to fostering resilience and preparedness within the school community. Through engaging awareness campaigns in student forums and the creation of informative disaster posters, the team empowers students to take charge of their safety. By developing clear evacuation route plans and installing guiding directional signs, they are enhancing the schools readiness for any challenge. The completion of disaster surveys further solidifies this proactive approach. As a result, students have experienced a remarkable growth in their understanding of disaster mitigation, equipping them with the knowledge to face the future with confidence